Oxalato bridged coordination polymer of manganese(iii) involving unconventional O⋯π-hole(nitrile) and antiparallel nitrile⋯nitrile contacts: antiproliferative evaluation and theoretical studies. (12th November 2020) - Dutta, Debajit; Sharma, Pranay; Frontera, Antonio; Gogoi, Anshuman; Verma, Akalesh K.; Dutta, Diksha; Sarma, Bipul; Bhattacharyya, Manjit K.
Abstract : Unconventional O⋯π-hole(nitrile) and antiparallel nitrile⋯nitrile contacts have been theoretically investigated for a Mn(iii ) coordination polymer considering cytotoxicity, apoptosis, ROS generation, molecular docking and pharmacophore features. Abstract : A new oxalato bridged polymeric Mn(iii ) coordination compound, {[Mn2 (η 2 -C2 O4 )(H2 O)2 Cl4 ] 2(4-CNpy)} n (1 ) (C2 O4 = oxalate, 4-CNpy = 4-cyanopyridine), has been synthesized and characterized using elemental analysis, and spectroscopic (IR, electronic, XPS) and single crystal X-ray diffraction techniques. Electronic and XPS analyses of the compound justify the presence of a Mn(iii ) center that is charge compensated by the two chlorido ligands and the oxygen atom of the bridged oxalate. 4-CNpy molecules in the lattice form unconventional H-bonded supramolecular dimers in the solid state assisted by antiparallel CN⋯CN dipole⋯dipole interactions, which has been confirmed using QTAIM and NCI plot analysis and supported by MEP surface analysis. Remarkably, this dimer concurrently establishes a weak anion–π interaction with the coordinated chlorido ligand. Unexpectedly, QTAIM analysis reveals the existence of an interesting O⋯π-hole(nitrile) contact involving the coordinated water molecule and the nitrile moiety that also contributes to the stabilization of the dimer in the crystal structure. To the best of our knowledge, the existence of such π-hole interaction involving nitrile derivatives has not been reported before. Compound 1 has been further screened for anticancer activity in the malignant Dalton's lymphoma (DL) cell line and the results were confirmed by molecular docking and pharmacophore features. Our findings indicated that the cytotoxicity of compound 1 is initially increased in a dose dependent manner (0.01–1 μM) and then decreased (5–10 μM), which is also affected by the reactive oxygen species (ROS) in the cells. Interestingly, very low cytotoxicity (5–14%) was observed in the case of healthy cells (PBMC) for similar experimental conditions.